Socioeconomic Characteristics and Depression in Canada: A Comparison between Females and Males - Yao, Karen (Université d'Ottawa | University of Ottawa, 2017)
Mental health and economic well-being are strengthened when the causes and implications of depression are addressed. This paper uses data from the 2012 Canadian Community Health Survey – Mental Health component to analyze the impact of personal, work, family, and health and behaviour characteristics on the probability of being depressed. I analyze the impact on depression firstly for the whole population, followed by a comparison of the outcomes between females and males. I find that females are 5 to 7 percentage points more likely to be depressed than males, no matter the specification used. When all the characteristics are studied separately, by gender, we see that work characteristics such as low income or unemployment increases depression for males only. For females only, family characteristics such as having a child decreases depression, though being divorced, separated, or widowed instead of being married increases depression. Drug dependence increases the likelihood of being depressed for females more than males, while alcohol abuse only affects females. An Oaxaca decomposition further yields a total explained effect of zero, as well as a significant constant in the unexplained part, both of which affirm that females are more depressed than males.